Brief review of dinosaur studies and perspectives in Brazil - KELLNER,ALEXANDER W. A. (2000)
Dinosaur research is developing at very high rates around the world resulting in several new discoveries that are improving our understanding of this terrestrial reptilian clade. Except for the last couple years, the studies of Brazilian dinosaurs have not followed this expansive trend, despite the high potential of several dinosaur localities. So far there are only eight described taxa, four in the last year, representing theropod, sauropod, and one possible prosauropod taxa. Except for footprints, there are no records of ornithischian dinosaurs in the country what is at least partially explainable by the lack of continuous vertebrate fossil collecting program in the country. More funding is necessary to improve the research activities in this field.